What would it take to make a hoverboard? - Amin, Anita Nahta (Capstone Press, 2020)
"In science fiction, hoverboard users glide above sidewalks on machines that look like skateboards with no wheels. How could one of these floating boards be created? Scientists have some ideas, which include using powerful magnets. Discover the science and technology behind what it would take to make a real-life hoverboard!"--
Floating on air -- What is a hoverboard? -- How would a hoverboard work? -- Current hoverboard technology -- What technology is needed? - What could the future look like?
Includes index.
Grades 4-6
Keywords: Ground-effect machines -- Juvenile literature; Personal propulsion units -- Juvenile literature; Technological innovations -- Juvenile literature; Instructional and educational works